Adiponectin fine‐tuning of liver regeneration dynamics revealed through cellular network modelling. (15th January 2015) - Correnti, Jason M.; Cook, Daniel; Aksamitiene, Edita; Swarup, Aditi; Ogunnaike, Babatunde; Vadigepalli, Rajanikanth; Hoek, Jan B.
Abstract : Key points: Loss of adiponectin delays the initiation of liver regeneration after partial hepatectomy, but later accelerates regeneration. Loss of adiponectin modulates these regeneration kinetics through decreased hepatocyte response to inflammation and increased growth factor bioavailability. Increased adiponectin suppresses liver regeneration through decreased growth factor bioavailability. Our predictive computational model was able to connect these molecular regulatory events to tissue physiology. Abstract: Following partial hepatectomy, the liver initiates a regenerative programme involving hepatocyte priming and replication driven by the coordinated actions of cytokine and growth factors. We investigated the mechanisms underlying adiponectin's (Adn) regulation of liver regeneration through modulation of these mediators. Adn –/– mice showed delayed onset of hepatocyte replication, but accelerated cell cycle progression relative to wild‐type mice, suggesting Adn has multiple effects fine‐tuning the kinetics of liver regeneration. We developed a computational model describing the molecular and physiological kinetics of liver regeneration in Adn –/– mice. We employed this computational model to evaluate the underlying regulatory mechanisms. Our analysis predicted that Adn is required for an efficient early cytokine response to partial hepatectomy, but is inhibitory to later growth factor actions. Consistent with this prediction, Adn knockout reduced hepatocyte responses to interleukin‐6 during the priming phase, but enhanced growth factor levels through peak hepatocyte replication. By contrast, supraphysiological concentrations of Adn resulting from rosiglitazone treatment suppressed regeneration by reducing growth factor levels during S phase, consistent with computational predictions. Together, these results revealed that Adn fine‐tunes the progression of liver regeneration through dynamically modulating molecular mediator networks and cellular interactions within the liver.